Application of Thomas Model to Determine the Capacity of Bintaro Fruit Shell Adsorbent - Timothy Blessing; Okik Hendriyanto; Euis Nurul Hidayah; Anis Artyani (Nusantara Science and Technology Proceedings)
The increase in the electroplating industry resulted in a large number of heavy metal wastes that are harmful to the environment, for example, hexavalent chromium waste. The Bintaro which contains cellulose is considered as a potential adsorbent to remove heavy metals. Therefore, a comparative study on the adsorption capacity of continuous adsorption was carried out in reducing the concentration of heavy metal Cr6+ in electroplating wastewater. The characterization itself can be done by testing the moisture content and ash content and SEM testing. The study of the adsorption capacity in a continuous process is generally carried out with Thomas modeling, where this research is carried out by a continuous adsorption process with variations in the adsorbent mass of 50 grams, 100 grams, 150 grams, 200 grams, and 250 grams. The best results were obtained to remove Cr6+ metal which was 94.4% in the Bintaro shell adsorbent type with a mass of 250 grams. The continuous adsorption process obtained the highest Thomas constant (Kth) value and the highest adsorption capacity (qo), namely using Bintaro shell activated carbon with a mass of 250 grams with an absorbance capacity value of 0.443mg / g. The results showed that the activated carbon of Bintaro shell showed that they were quite effective as adsorbents in the adsorption process to remove heavy metal Cr6+